Math, asked by akankshai560gmailcom, 1 year ago

limit X tends to zero root x + 4 minus 2 upon root x + 9 - 3

Answers

Answered by Anchalsinghrajput
6
heya your answer is here .... hope it helps
Attachments:
Answered by Anonymous
4

Answer:

3/2

Step-by-step explanation:

\displaystyle\frac{\sqrt{x+4}-2}{\sqrt{x+9}-3}\\\\=\frac{(\sqrt{x+4}-2)(\sqrt{x+4}+2)(\sqrt{x+9}+3)}{(\sqrt{x+9}-3)(\sqrt{x+9}+3)(\sqrt{x+4}+2)}\\\\=\frac{((x+4)-4)(\sqrt{x+9}+3)}{((x+9)-9)(\sqrt{x+4}+2}\\\\=\frac{x(\sqrt{x+9}+3)}{x(\sqrt{x+4}+2)}\\\\=\frac{\sqrt{x+9}+3}{\sqrt{x+4}+2}\\\\\rightarrow\frac{\sqrt9+3}{\sqrt4+2}\ \text{as}\ x\rightarrow 0\\\\=\frac64\\\\=\frac32


akankshai560gmailcom: thanks for the reply
Anonymous: You're welcome. Glad to help.
akankshai560gmailcom: it's realy works of me
Similar questions